Presumed Guilty - Hernandez, Roberto; Smith, Geoffrey (Instituto Mexicano de Cinematografia, 2008)
Verzio FF "Presumed Guilty" uncovers staggering facts about the Mexican judicial system: 93 percent of defendants never see a judge; 93 percent of inmates are never shown their arrest warrant; 95 percent of verdicts are "guilty"; 92 percent of verdicts are based on no physical evidence; police officers are rewarded for the number of arrests they make; and any court official can preside over court hearings (not just judges). The film focuses on the case of Jose Antonio Zuniga Rodriguez, who was incarcerated in 2005, accused of killing someone he claims he did not know, and sentenced to 20 years in prison. Two young Mexican attorneys attempt to exonerate the wrongly convicted man by making a documentary. A film about the contradictions of a judicial system that presumes suspects guilty until they are proven innocent.